The moduli space of N=1 superspheres with tubes and the sewing operation - Barron, Katrina, 1965- (Memoirs of the American Mathematical Society ;, 2003)
Introduction An introduction to the moduli space of $N=1$ superspheres with tubes and the sewing operation A formal algebraic study of the sewing operation An analytic study of the sewing operation Bibliography.